2015
DOI: 10.18034/abr.v1i1.334
|View full text |Cite
|
Sign up to set email alerts
|

Is the Stock Market Overvalued: A Study in the Context of Bangladesh?

Abstract: The primary objective of this paper is to analyze if the Market overvalued. We studied prices of 17 actively companies in the Market from 2006 to 2010 and used three Valuation Ratios with an explicit corporate sector along with overall market index data and found that the Stock Marke overvalued. The analysis was completed in two stages. At first we analyzed each of the 17 companies to determine the condition of each company .This part shows that among 17 companies most of the companies' share prices are overva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…A study on 2006 to 2010 data incorporating 17 companies, using three valuation ratios, found that the stock market of Bangladesh was overvalued. The analysis also found a relationship between mass capital accumulation and overvalued market [1]. Many people believe that the 2010-11 stock market crash in Bangladesh was more likely to be a correction after the market's apparent overheating.…”
Section: Money Making Psychologies Behind Stock Market Crash In Banglmentioning
confidence: 85%
“…A study on 2006 to 2010 data incorporating 17 companies, using three valuation ratios, found that the stock market of Bangladesh was overvalued. The analysis also found a relationship between mass capital accumulation and overvalued market [1]. Many people believe that the 2010-11 stock market crash in Bangladesh was more likely to be a correction after the market's apparent overheating.…”
Section: Money Making Psychologies Behind Stock Market Crash In Banglmentioning
confidence: 85%